Genetic dissection of hundred-kernel weight through combined genome-wide association study and linkage analysis in tropical maize - Mengfei Shi; Fuyan Jiang; Ranjan K. Shaw; Babar Ijaz; Jiachen Sun; Xingming Fan (BMC Genomics)
Abstract Background Hundred-kernel weight (HKW) is a crucial determinant of maize yield. Understanding the genetic mechanisms underlying HKW is vital for maize breeding programs aimed at enhancing productivity. This study aimed to explore the genetic basis of HKW in maize using a multi-parent population (MPP), developed by crossing the common male parent Ye107 with five female parents representing a range of kernel sizes and weights. The MPP was evaluated under two distinct environmental conditions (19DH and 19BS). Results Genotyping-by-sequencing (GBS) identified 591,483 high-quality single nucleotide polymorphisms (SNPs), which were used for a genome-wide association study (GWAS) and linkage analysis. The GWAS revealed 21 SNPs significantly associated with HKW, with Zm00001d028188, a gene involved in cell wall synthesis, emerging as a key candidate located on chromosome 1. This gene, encodes Galacturonosyltransferase 1 (GAUT1) and overlapped with two identified quantitative trait loci (QTLs): qHKW1-2 and qHKW1-3, which were further validated through linkage analysis. Conclusions This study identified critical genetic loci and candidate genes, such as Zm00001d028188, involved in regulating HKW in maize. The findings provide valuable genomic resources for maize breeding, potentially contributing to the development of high-yielding maize varieties through an enhanced understanding of the genetic control of HKW.